Robust active noise control in a car cabin: Evaluation of achievable performances with a feedback control scheme. (December 2018) - Loiseau, Paul; Chevrel, Philippe; Yagoubi, Mohamed; Duffal, Jean-Marc
Abstract: The application dealt with in this paper is the active attenuation of broadband noise (produced by the tire/road contact) in a car cabin, using only a feedback control scheme (1-DOF (one degree of freedom)). The objective of the proposed control methodology is to evaluate achievable performances according to the frequency bandwidth in which attenuation is desired. This is investigated numerically, by seeking a multi-input multi-output (MIMO) active noise control solution that reaches the best attenuation level, under explicit robustness constraints. The paper aims to (i) formalize the underlying optimization problem including performance and robustness indicators as well as industrial constraints, (ii) perform an effective MIMO identification, and (iii) provide an a priori control structure and then proceed to direct optimization of some meaningful parameters using a well-suited nonsmooth optimization solver. Finally, the simulation and experimental results obtained following the proposed methodology are shown and discussed. Highlights: Robust broadband noise attenuation in car cabins by feedback is considered. Indicators for the evaluation of ANC applications are presented in detail. Achievable performances of the considered ANC application are precisely evaluated. Results are validated experimentally on a demonstrator and a vehicle prototype.